The People's Republic of China's long-run growth through the lens of the export-led growth model - Jesus Felipe; Matteo Lanzafame (Asian Development Bank (ADB), 2018)
The People's Republic of China's (PRC) remarkable growth performance over the last 3 decades has been associated to very robust export growth, so much so that many refer to it as a clear example of export-led growth (ELG). Using the concept of the balance-of-payments equilibrium (BOPE) growth rate, which provides a framework to test the ELG hypothesis, we show that the PRC's actual long-run growth is well approximated by its BOPE growth rate. This growth rate is given by the ratio of the growth rate of exports to the income elasticity of imports. We estimate the latter using the Kalman filter, which allows us to obtain a time-varying estimate of the PRC's BOPE growth rate. We find that the average value of the PRC's BOPE growth rate during 1981-2016 was 11%, but it varied significantly over time and declined notably after 2007. Today, it is estimated at a much lower 5.9%. We then discuss the determinants of the PRC's BOPE growth rate and of the income elasticity of imports, with the help of the Bayesian model averaging technique. The analysis highlights the role of the composition of aggregate demand as the main driving force, both for its direct effects on the income elasticity of imports, and for the indirect effects on export growth via capital accumulation, in particular fixed asset investment. Our analysis has important implications to understand the PRC's transition to a "New Normal" of a lower growth rate.
Keywords: E24; E32; O14; O47; O50; 330; balance-of-payments equilibrium growth rate; Bayesian model averaging; export-led growth; Kalman filter; People's Republic of China